Femtosecond photon-number squeezed light generation in AlGaAs waveguides - Ward, M; Kastner, B; Ju, H; Brown, J; Fox, A; Ryan, J (2001)
We show that photon number squeezing of femtosecond optical pulses occurs in an AlGaAs waveguide due to the incoherent nonlinear process of multi-photon absorption. Further, we show that self-phase modulation in conjunction with spectral filtering give rise to enhanced photon-number squeezing.